Theoretical assumptions of Maffesoli's sensitivity and Problem-Based Learning in Nursing Education - María-Aurora Rodríguez-Borrego; Rosane Gonçalves Nitschke; Marta Lenise do Prado; Jussara Gue Martini; María-Dolores Guerra-Martín; Carmen González-Galán (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVE: understand the everyday and the imaginary of Nursing students in their knowledge socialization process through the Problem-Based Learning (PBL) strategy.METHOD: Action Research, involving 86 students from the second year of an undergraduate Nursing program in Spain. A Critical Incident Questionnaire and Group interview were used. Thematic/categorical analysis, triangulation of researchers, subjects and techniques.RESULTS: the students signal the need to have a view from within, reinforcing the criticism against the schematic dualism; PBL allows one to learn how to be with the other, with his mechanical and organic solidarity; the feeling together, with its emphasis on learning to work in group and wanting to be close to the person taking care.CONCLUSIONS: The great contradictions the protagonists of the process, that is, the students experience seem to express that group learning is not a form of gaining knowledge, as it makes them lose time to study. The daily, the execution time and the imaginary of how learning should be do not seem to have an intersection point in the use of Problem-Based Learning. The importance of focusing on the daily and the imaginary should be reinforced when we consider nursing education.